2022
DOI: 10.2147/opth.s391319
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Suprachoroidal Injection of Triamcinolone Acetonide in Resistant Diabetic Macular Edema Using a Modified Microneedle

Abstract: The present study evaluated the effectiveness of suprachoroidal injection of triamcinolone acetonide (TA) in resistant diabetic macular edema (DME) using a modified microneedle. Patients and Methods: This is a prospective nonrandomized interventional study that was conducted on 55 eyes of 39 patients with centrally involving DME resistant to previous antivascular endotheli qal growth factor (VEGF) agents. All patients received suprachoroidal injection of triamcinolone acetonide 4 mg/0.1 mL by a modified specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Our findings were consistent with the study conducted by Nawar, who also observed a significant rise in IOP with the use of suprachoroidal triamcinolone after 1 month but no significant rise at 3, 6, 9 and 12 months after injection. 8 Most other studies included in this meta-analysis all noted a rise in IOP 1 and 3 months after injecting suprachoroidal triamcinolone but interestingly, this rise was not statistically significant and was associated with a p -value >0.05. 9 10 , 22 26 The exceptions to this were the studies by Abdelshafy Tabl et al and Ateeq et al .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our findings were consistent with the study conducted by Nawar, who also observed a significant rise in IOP with the use of suprachoroidal triamcinolone after 1 month but no significant rise at 3, 6, 9 and 12 months after injection. 8 Most other studies included in this meta-analysis all noted a rise in IOP 1 and 3 months after injecting suprachoroidal triamcinolone but interestingly, this rise was not statistically significant and was associated with a p -value >0.05. 9 10 , 22 26 The exceptions to this were the studies by Abdelshafy Tabl et al and Ateeq et al .…”
Section: Discussionmentioning
confidence: 77%
“… 6 Suprachoroidal injections of triamcinolone acetate are currently gaining traction after promising results in large clinical trials, due to less observed drug bioavailability in the anterior segment and significantly greater spread to the retina and choroid. 7 9 This technique involves injecting into the suprachoroidal space, which is a potential space between the choroid and sclera. 10 Due to lower penetrance into the anterior chamber, it was hoped that this technique would reduce the adverse effects commonly associated with ocular corticosteroid use.…”
Section: Introductionmentioning
confidence: 99%
“…TA is not approved for intraocular use, but it is used off-label to treat vitreoretinal diseases in a dose ranging between 1 and 4 mg [ 78 ], with functional and anatomical efficacy within 3–6 months post-injection [ 79 ]. Two other administration routes of TA tested in DME eyes, the posterior sub-tenon injection of 20 or 40 mg of TA [ 80 ] and the suprachoroidal injection of 2 or 4 mg of TA [ 81 ], have shown results comparable to those obtained with the IV TA injections, with less side effects. There is a preservative-free TA approved for intraocular use, though it is not for DME per se and not easily available, Triesence (Alcon Pharmaceuticals, Ft. Worth, TX, USA).…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 99%
“…In conclusion, although IVTA has shown to be effective in DME management, its short duration of action and the high incidence of IOP elevation and cataract development, especially in younger patients, have limited its use in favor of other approved intravitreal CSs. More recently, TA administered as supra-choroidal [ 81 , 99 ] and sub-tenon injections [ 80 ] in DME eyes has shown promising although time-limited results.…”
Section: Corticosteroids For the Management Of Dmementioning
confidence: 99%
“…Several nonrandomized, single-arm studies have also provided evidence supporting the effectiveness of SCTA in improving BCVA and reducing CST with minimal AEs [ 110 , 111 , 112 , 113 , 114 , 115 ]. However, a study by Tharwat and colleagues (2022) suggests that formulated posterior subtenon TA (PSTA) injection may offer better outcomes for managing rDME with reduced risk of IOP elevation.…”
Section: Suprachoroidal Injection In Ocular Diseasesmentioning
confidence: 99%